Pemberdayaan Majelis Taklim Melalui Metode Wafa: Strategi Belajar Al-Qur'an Efektif dengan Pendekatan Otak Kanan - Raudatussolihah, Baiq; Rasjusti, Nurul Ilmi; Mutmainnah, Mutmainnah; Kholida, Masita Taufiqi; Rais. TM, Ahmad (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2025)
This community service activity aims to empower members of the Majelis Taklim in improving the quality of learning the Qur'an through the Wafa Method. This method combines a right-brain approach that emphasizes imagination, rhythm, and visualization to memorize and understand the Qur'an in a fun, effective and efficient way. The target of this activity is the Majelis Taklim which has so far used conventional methods in learning the Qur'an. Training is provided in the form of interactive workshops and intensive mentoring for one month. The results show an increase in enthusiasm, reading skills, and memorization of the Qur'an of the participants. The right-brain approach has been proven to help participants focus more and enjoy the learning process. Thus, the Wafa Method can be used as a fun, effective and efficient empowerment strategy to improve understanding of the Qur'an in the Majelis Taklim environment.